Implementasi Komponen Pendidikan Terhadap Penyelenggaraan Program Studi Strategi Operasi Laut Program Magister Terapan di Seskoal - Oni Wiyono (Universitas Indraprasta PGRI, 2020)
Seskoal (Naval Command and Staff College) as a Center of Excellence on Naval and Maritime has made a commitment to make the innovations in quality and development as a centre of Navy officers of Maritime and Navy qualificationa in shaped the research,inspection, and serving to the society through the applied magister navy operation strategis study program.This research is about educations components in Seskoal reguler educations that for enhancing the quality Seskoal especially for the accreditation from B to A.It explains about the parts of components of educations; the curricullum,internet, and librarian Seskoal.The methode using the qulitatitive way, the data processor using the Software Nvivo 12 Plus, and the Trianggulasi for the analizer.The results of this research are the implementations ef components educations giving the impact of the excercise Seskoal reguler educations which keep on moving in 10 months or in 44 weeks, 55 sks loads,and 2,330 lessons hours @ 50 minutes. Onthe other hand, this educations component is also for the requirements of BAN-PT regardings Seskoal accreditaions.